1845 Iowa Laws 119, An Act to Incorporate and Establish the City of Dubuque, chap 123, § 12 - (:unkn) unknown (General Publisher, 1845)
The city of Dubuque shall have the authority to regulate the storage of gun powder.
--
Keywords: GUN POWDER STORAGE